Thickness effect of micro speaker copper coil fabrication process - Ayat, F.L.; Moghavvemi, M.; Attaran, A. (IFSA, 2011)
This paper present the advantage of using electroplating for making the thick layer of copper over the sputtering. The purpose of this paper is to fabricate the copper coil for microspeaker. The design and simulation of this copper coil shows that the 15 um thickness is needed. In order to fabricate this coil, copper plating is used. The electro-deposition process is well suited to make films of metals such as copper, gold and nickel. The films can be made in any thickness from ~1 μm to >100 μm. The deposition is best controlled when used with an external electrical potentiostate. However, it requires electrical contact to the substrate when immersed in the liquid bath. In any process, the surface of the substrate must have an electrically conducting coating before the deposition can be done. The result of this experimental research shows the easy and cheap way to fabricate the thick layer of copper for microspeacker fabrication.